ANALISIS TINGKAT USABILITY APLIKASI EDUKASI RUANGGURU MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) - Iqbal Sidiq (LPPM Universitas Abdurrab, 2026)
Ruangguru is one of the most widely used digital tutoring platforms by students in Indonesia; however, dynamic interface updates have the potential to affect system usability. This study aims to evaluate the interface quality and user experience of the Ruangguru application using the System Usability Scale (SUS) method. Primary data collection was conducted online using a purposive sampling technique, involving 30 active respondents in the Purwokerto region dominated by teenage students (96.67%) with varying durations of use. The evaluation focused on two standard industry assessment parameters, namely Acceptability Ranges and Grade Scale. The results of the questionnaire raw data processing showed an accumulated conversion value of 857 with a total score of 2142.5, yielding a global average SUS score of 71.4. This score maps the usability performance of the Ruangguru application into the Acceptable zone and places it in the Grade C category. Based on the item statement analysis, the system's core strengths lie in the high interest for routine use (Q1) and the ease of learning the system quickly (Q7). However, identified barriers were still found in the consistency of visual elements across pages (Q6). This research contributes recommendations for developers to harmonize graphic design and simplify sub-menu navigation in subsequent version updates to mitigate user cognitive load.